المقياس الملائم لقياس جودة الخدمة المصرفية المدركة في المصارف السورية - العمار, رضوان; صقر, أحمد; نورالله, مصطفى (Latakia University Journal - Economic and Legal Sciences Series, 2013)
هدفت هذه الدراسة إلى التعرف على مفهوم قياس جودة الخدمة المصرفية وأهميتة بالنسبة للمصارف ، كما سلطت الضوء على بعض نقاط الاختلاف الجوهرية بين البلدان المتقدمة والبلدان النامية في مجال قياس جودة الخدمة المصرفية وعرضت هذه الدراسة ستة مقاييس تناسب بيئة العمل المصرفي في سورية تم انتقاؤها وفق معايير مناسبة ذلك للوصول إلى مقاييس تقترب من واقع العمل المصرفي في سورية و تمت مناقشة كل من هذه المقاييس على حدة، واستنتج الباحث أن المقياس الخامس Abdullah et al هو أكثر المقاييس ملاءمةً للمصارف السورية . إلا أن الدراسة أوصت بأهمية تصميم مقاييس تلائم بيئة العمل المصرفية في سورية بحيث تعمل على قياس جودة الخدمة المصرفية بأدق ما يمكن . This study aims to identify the concept of Measuring the Quality of Banking Services (MQBS) and its importance to banks. It also highlights some major points of disagreement between developed and developing countries in the field of measuring MQBS and offers six scales which fit the banking sector in Syria. These scales were selected according to appropriate criteria; therefore every scale was discussed separately. The researcher concludes that scale number five Abdullah et al is the most appropriate scale for the Syrian bank sector. However, the study points out to the importance of designing a new scale based on the working environment of the Syrian banking sector and is able to measure the quality of banking services as accurate as possible.